Impact of External Conditions on the Desorption and Degradation Capacity of Biochar for Rhodamine B - Chenghong Ao; Mai Shan; Yue Zhang; Xiang Li; Ying Kong; Xinwei Dong; Yang Liu; Danping Wu (Molecules)
Biochar has attracted considerable interest owing to its high adsorption capacity; however, the mechanisms through which environmental factors influence the release of adsorbed pollutants remain unclear. This study investigates the adsorption and desorption dynamics of Rhodamine B (RhB) on biochars B2 and B6, which were pyrolyzed at temperatures of 200 °C and 600 °C, respectively, under varying conditions. The results indicated that there was no significant difference in removal efficiency at low RhB concentrations; however, at a concentration of 600 mg/L, biochar B2 had a higher removal efficiency than B6, likely attributable to more adsorption sites. Increased temperatures were found to enhance desorption from both B2 and B6, with B6 exhibiting a faster desorption rate. This phenomenon may be due to the stronger hydrogen bonding between B2 and RhB, which could inhibit desorption. In addition, elevated pH values facilitated desorption, presumably through electrostatic repulsion. Under alkaline conditions, B2 released a greater amount of dissolved organic matter (DOM), leading to increased RhB desorption relative to B6. This study offers a valuable reference for evaluating the environmental risk associated with the application of biochar in real-world settings.